Cytotoxin-Associated Gene A-Negative Helicobacter pylori Promotes Gastric Mucosal CX3CR1+CD4+ Effector Memory T Cell Recruitment in Mice - Sun, Heqiang; He, Taojun; Wu, Yanan; Yuan, Hanmei; Ning, Jie; Zhang, Zhenhua; Deng, Xinli; Li, Bin; Wu, Chao (Frontiers in Microbiology, 2022)
Background: Helicobacter pylori can cause many kinds of gastric disorders, ranging from gastritis to gastric cancer. Cytotoxin-associated gene A (CagA)+H. pylori is more likely to cause gastric histopathologic damage than CagA−H. pylori. However, the underlying mechanism needs to be further investigated. Materials and methods: Mice were intragastrically administered equal amounts of CagA+ or CagA−H. pylori. Four weeks later, 24 chemokines in stomachs were measured using a mouse chemokine array, and the phenotypes of the recruited gastric CD4+ T cells were analyzed. The migration pathway was evaluated. Finally, the correlation between each pair among the recruited CD4+ T cell sub-population, H. pylori colonization level, and histopathologic damage score were determined by Pearson correlation analysis. Results: The concentration of chemokines, CCL3 and CX3CL1, were significantly elevated in CagA−H. pylori-infected gastric mucosa than in CagA+H. pylori-infected gastric mucosa. Among them, CX3CL1 secreted by gastric epithelial cells, which was elicited more effectively by CagA−H. pylori than by the CagA+ strain, dramatically promoted mucosal CD4+ T cell migration. The expression of CX3CR1, the only known receptor of CX3CL1, was upregulated on the surface of gastric CD4+ T cells in CagA−H. pylori-infected stomach. In addition, most of the CX3CR1-positive gastric CD4+ T cells were CD44+CD69−CCR7− effector memory T cells (Tem). Pearson correlation analysis showed that the recruited CX3CR1+CD4+ Tem cell population was negatively correlated with H. pylori colonization level and histopathologic damage score. Conclusion: CagA−H. pylori promotes gastric mucosal CX3CR1+CD4+Tem recruitment in mice.